Weegy: First, recognize that this format follows that of a difference of two squares: a^2 - b^2. How would you factor this? (a + b)(a - b). [ (Try it: you get a^2 + ab - ab - b^2 = a^2 - b^2)
So, what are the square roots of each of the terms above? sqrt of 16p^4 = 4p^2 and sqrt(625q^4) = 25q^2
So, you get (4p^2 - 25q^2)(4p^2 + 25q^2)
You can't stop here, however, because you have another difference of two squares in the first term. The second term is not factorable without including imaginary numbers, so let's leave it as it is.
Following the above procedure for 4p^2 - 25q^2, you get sqrt(4p^2) = 2p and sqrt(25q^2) = 5q
So, 4p^2 - 25q^2 = (2p - 5q)(2p + 5q)
Substituting this back, you get the final answer:
16p^4 - 625q^4 = (2p - 5q)(2p + 5q)(4p^2 + 25q^2) ] User: Factor x4y2 + x3y3 Weegy: monomial (More)

There are no comments.